Improving On-Time Delivery through Supply Chain Collaboration: The Experience of Brewery Firms in South-South, Nigeria - Igwe, Sunny R; Robert, Coker Preye; Chukwu, God’swill C (Journal of Asian Business Strategy, 2016)
In today’s competitive environment, firms are no longer internally sufficient. This implies that for organization to increase in performance, informational and relational synergies is encouraged among supply chain participants. The purpose of this paper is to investigates supply chain collaborative activities on On-time delivery. Employing stratified sampling technique and with questionnaire, 210 brewery firms, distributors and retailers supplied the data. Pearson product moment correlation and multiple regressions were used for test of hypothesis. The findings reveal specifically that dedicated investment, information sharing, decision synchronization and incentive alignment have significant and positive influence on (on-time delivery). This suggests that supply chain collaboration effect on time delivery. To harness competitive edge of on- time delivery, brewery firms should strategically share in plan, build, and ensure collaborative activities cut across all the trading partners and instill trust building in process in the supply chain.